Unravelling the diversity and distribution of the soybean rust fungus Phakopsora pachyrhizi in east Africa - Murithi, H.M. (Wageningen University & Research, 2019)
Soybean is an important legume crop that is cultivated worldwide on more than 120 million hectares, producing more than 330 million tonnes of soybeans annually. Soybeans contain 40% of protein and 20% of oil and the crop is therefore used both for human and livestock consumption. Generally, soybean has the potential to significantly improve the nutrition of the inhabitants of sub-Saharan Africa. Soybean production has intensified in Africa over the past 15 years, owing to the raising demand driven by a population increase and a desire for diversification of diets. In addition, soybean cultivation contributes to increased economic opportunities and higher living standards for farmers. However, soybean yields in Africa on average range between 0.8 to 1.2 tonnes/ha, while the potential of the crop can be as high as 4 tonnes/ha. The relatively poor yields can largely be attributed to abiotic factors (soil fertility, drought, poor nodulation) as well to as biotic ones (diseases and insect pests).